A reurbanização modernizada do moderno - Castello, Lineu; Machry, Juliana; Petroli, Marcos Amado (7º Seminário Docomomo Brasil, Porto Alegre, 2007, 2007)
contemplate, behind the call for papers for the 7th DOCOMOMO, the opportunity for discussing the challenging topic of urban sustainability that is increasingly faced by 21st century architects and urbanists. The motto in the Call for Papers that states ‘the modern already passed; the past in the modern’ fits splendidly to the topic and enables the issuing of lessons on how to keep survival viable in/of the planet. Certain cares taken, policies destined to keep cities growing by the reuse of inner abandoned spaces presents merit beyond any doubt. This theme will be approached in the present text, through an emblematic experience as empirical counterpoint: Shanghai’s Bund. Several topics – all remarkable – related to contemporary rearchitecture matters, seem to come together in the Bund. Since the early times of its urbanization, the area has always been perceived by residents in a distinguished way. Sometimes being perceived by Europeans as a European place; sometimes perceived as a place by natives; but always being perceived as a place. And a place where that quality inherent to urban spaces – urbanity – grows generously. In early 20th century, when its urban development reaches a peak, the Bund becomes a showcase of the most advanced technological achievements, displaying, to the agricultural society of the time, the modernity of an urban environment. Along Bund’s strip, of approximately 2 km long, there are architectural works of various influences, including extracts of neoclassic and art-deco origins. In the late 20th century, the area experiences a reurbanization, aiming to transform Shanghai into a modern global metropolis, able to exert a powerful allure over visitors, dwellers, tourists and investors. It is in this new condition that the Bund is approached in this paper: as a place. A place that provides a magnificent illustration of today’s successful rearchitecture actions.
Keywords: lugar urbano; rearquitetura; estágio de modernidade